Poles and Italians then, Mexicans Now? Immigrant-to-native wage ratios, 1910 and 1940 - Joel Perlmann (Levy Economics Institute of Bard College, 2002)
A good deal of recent discussion among social scientists concerned with immigration is about the disadvantages faced by immigrants who enter the U. S. labor force with much-lower levels of skills than those possessed by the typical native white worker. Among contemporary immigrant groups, by far the most important example is the Mexicans. The challenges faced by such an immigrant today are often contrasted with the challenges faced by low-skilled immigrants who entered the U. S. during the great immigration wave of 1890-1920-most notably Poles, other Slavs, and Italians. In articles published at the end of 2001 in the New York Review of Books, Christopher Jencks drew on research by George Borjas to argue that the wage ratios of Mexicans compared to relevant U.S. workers today were far worse than the comparable wage ratios of new immigrants compared to native white workers in 1910. Jencks argues for a reconsideration of immigration policy, especially regarding Mexico. This paper explores the nature of the early evidence in detail. A good deal of ambiguity is involved in the materials, but tests made to date do not contradict Jencks's conclusions about wage ratios during the earlier immigration. The paper draws evidence from IPUMS census datasets from 1900, 1910, 1940, and 1950.
Keywords: 330